2013
DOI: 10.3390/su5104152
|View full text |Cite
|
Sign up to set email alerts
|

Disabled People and the Post-2015 Development Goal Agenda through a Disability Studies Lens

Abstract: Abstract:The purpose of this study was to examine the role and visibility of disabled people in the discourses of various global policy processes related to sustainable development and the Post-2015 development agenda. This article makes several recommendations for strengthening the role of disabled people in these discourses. The research addresses the question of how the disability community and sustainable development community relate to each other in these discourses. This study provides quantitative and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The UN Convention on the rights of persons with disabilities, states in article 28: "States Parties recognize the right of persons with disabilities to an adequate standard of living for themselves and their families, including adequate food, clothing and housing, and to the continuous improvement of living conditions, and shall take appropriate steps to safeguard and promote the realization of this right without discrimination on the basis of disability" (United Nations, 2007). The lack of food security was mentioned numerous times by participants of a recent online consultation for a disability inclusive development agenda towards 2015 & beyond which was moderated by two leading international disability organizations and which gave voice to disabled people on numerous development issues (Wolbring, Mackay, Rybchinski, & Noga, 2013). Various sources reported on food insecurity experienced by disabled people (Hiranandani & Sonpal, 2010;D.…”
Section: Food Security and Disabled Peoplementioning
confidence: 99%
“…The UN Convention on the rights of persons with disabilities, states in article 28: "States Parties recognize the right of persons with disabilities to an adequate standard of living for themselves and their families, including adequate food, clothing and housing, and to the continuous improvement of living conditions, and shall take appropriate steps to safeguard and promote the realization of this right without discrimination on the basis of disability" (United Nations, 2007). The lack of food security was mentioned numerous times by participants of a recent online consultation for a disability inclusive development agenda towards 2015 & beyond which was moderated by two leading international disability organizations and which gave voice to disabled people on numerous development issues (Wolbring, Mackay, Rybchinski, & Noga, 2013). Various sources reported on food insecurity experienced by disabled people (Hiranandani & Sonpal, 2010;D.…”
Section: Food Security and Disabled Peoplementioning
confidence: 99%
“…There are of course many other contentious and multifaceted issues that need to be navigated by the SDG process; for example, issues of equity, the contested relationship between "good governance" and sustainability, and the visibility unevenness of certain social groups (Wolbring et al 2013). However, the Anthropocene poses particular challenges for how a strong and legitimate successor to the MDGs needs to be designed and formulated.…”
Section: Resultsmentioning
confidence: 99%
“…However, the same article mentioned that other targets of sustainable consumption are also covered such as food (n = 108), environment (n = 72), water (n = 66), products for households and people (n = 48), energy (n = 46), economics/income (n = 15), shrimps, living sea resources and forests (n = 11), tourism and electronics/technology and employees (n = 10). Two targets were mentioned (n = 8); one target (n = 6) and one target (n = 5); six targets were mentioned (n = 4) and six (n = 3) [110]. There were 14 targets that were mentioned (n = 2) and 29 targets that were mentioned (n = 1) [110].…”
Section: Sustainable Consumptionmentioning
confidence: 99%
“…Although the outcome documents seem to focus mostly on sustainable consumption in relation to natural resources, there are many areas outside of natural resources where sustainable consumption plays a role, such as healthcare [109]. A recent article [110] showed that if one searches Google Scholar TM (Mountain View, CA, USA) for "sustainable consumption" that the target for sustainable consumption mentioned the most was natural resources (n = 109) [110]. However, the same article mentioned that other targets of sustainable consumption are also covered such as food (n = 108), environment (n = 72), water (n = 66), products for households and people (n = 48), energy (n = 46), economics/income (n = 15), shrimps, living sea resources and forests (n = 11), tourism and electronics/technology and employees (n = 10).…”
Section: Sustainable Consumptionmentioning
confidence: 99%